2018
DOI: 10.1002/ccr3.1536
|View full text |Cite
|
Sign up to set email alerts
|

A young woman with steroid‐responsive, IgG4‐positive plasma cell‐enriched cystic lymphangioma and chylous ascites

Abstract: Key Clinical MessageLymphangiomas are benign tumors of the lymphatic vessels, which can be inflammatory and occasionally steroid‐responsive. IgG4‐related disease (IgG4‐RD) is a recently defined fibro‐inflammatory condition. We describe a novel association between reactive IgG4+ plasma cells and cystic lymphangioma in a young woman who had a dramatic clinical response to steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, the pathological examination did not reveal any fibrosis or obliterative phlebitis, and the authors concluded that their patient did not have IgG4-RD. 18 Both retroperitoneal fibrosis and lymphadenopathy have been observed in IgG4-RD, 19 but cystic forms of retroperitoneal fibrosis are an absolute rarity; only three of Length of lower image border: 2.33 mm (a, b) or 0.23 mm c, d).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pathological examination did not reveal any fibrosis or obliterative phlebitis, and the authors concluded that their patient did not have IgG4-RD. 18 Both retroperitoneal fibrosis and lymphadenopathy have been observed in IgG4-RD, 19 but cystic forms of retroperitoneal fibrosis are an absolute rarity; only three of Length of lower image border: 2.33 mm (a, b) or 0.23 mm c, d).…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathological examination did not reveal any fibrosis or obliterative phlebitis, and the authors concluded that their patient did not have IgG4-RD. 18 Both retroperitoneal fibrosis and lymphadenopathy have been observed in IgG4-RD, 19 but cystic forms of retroperitoneal fibrosis are an absolute rarity; only three of these cases are described in the literature, 20,21 and only one of them was punctured with evidence of chylous fluid. Fibrosis is more likely to cause a hydrocele or varicocele testis as a consequence of gonadal vessel involvement.…”
Section: Discussionmentioning
confidence: 99%